OC-031 INCIDENCE AND RISK FACTORS FOR RECURRENCE OF RIVES-STOPPA REPAIR FOR INCISIONAL HERNIAS. TWENTY-YEAR RETROSPECTIVE ANALYSIS OF LONG-TERM OUTCOMES OF DIFFERENT MESH REPAIRS. (13th October 2022) - Oprea, V; Toma, M; Buia, F; Leuca, D; Gheorghescu, D; Grad, O; Chiorescu, S
Abstract: Objective: the aim of this study was to determine the long-term recurrence and complication rates following Rives-Stoppa repair of midline incisional hernias with different types of synthetic materials. Patients and Methods: medical files of 1628 patients with midline incisional hernias who underwent abdominal wall reconstruction using Rives-Stoppa repair between January 1999 and December 2019 were reviewed. All patients followed up after 1 month, 6 months, and 1year later and after that yearly. Results: until 2007, 674 patients were operated on with available meshes for that time (mosquito net – 135, polyester mesh – 322, and polypropylene mesh – 217). After 2007, polypropylene meshes were used in 1054 patients (heavyweight in 428 patients and lightweight meshes in 626). The global recurrence rate after a mean follow-up of 96.5 months in the first group of patients was 13.3% and in the second group was 7.13% (mean follow-up of 108.4 months). The infection rate was 16.8% versus 9.2% with an increased incidence at 30 days (84 vs 62 patients). The hematoma rate was equally distributed. Seroma formation was almost 2.5-fold increased in the first group of patients (21.3% vs 8.7%). Increased rate of seroma formation were associated with mosquito net (OR = 1.7; 95% CI = 0.5–1.3; p=o.o2), heavyweight type type (OR = 0.9; 95 CI = 0.07–0.4; p=o.o31). Infection was associated with the usage of mosquito net, heavyweight type, and polyester mesh. Conclusions: the lightweight mesh offers a safe method for abdominal wall reconstruction.